Diverging patterns of cardiovascular diseases across immigrant groups in Northern Italy. (1st March 2018) - Fedeli, Ugo; Avossa, Francesco; Ferroni, Eliana; Schievano, Elena; Bilato, Claudio; Modesti, Pietro Amedeo; Corti, Maria Chiara
Abstract: Background: Only fragmentary data are available on the burden of non-communicable diseases among immigrants in Europe, mostly limited to mortality by cause. Aim of the study is to investigate the prevalence of cardiovascular diseases across different immigrant groups in the Veneto Region (North-Eastern Italy). Methods: The resident population aged 20–59 was classified according to country of citizenship. The Adjusted Clinical Groups System was adopted to identify selected cardiovascular conditions by linkage of Hospital Discharge Records, Emergency Room visits, Chronic disease registry for copayment exemptions, the Home care database, and drugs reimbursed by the Regional Health Service. Age standardized prevalence rates were compared across population groups, and rate ratios (RR) with 95% confidence intervals (CI) were computed taking the Italian population as reference. Results: The prevalence of diabetes was higher across all immigrant groups compared to Italians. Specific risk patterns could be identified associated to different ethnicities: South Asian immigrants were at very high risk of diabetes, dyslipidemia, and ischemic heart disease (males RR 2.3, CI 1.9–2.8; females RR 2.0, CI 1.2–3.5). Immigrants from Africa were affected by high rates of hypertension, cerebrovascular diseases, and heart failure, with a more pronounced unfavorable profile among females (hypertension RR 3.0, CI 2.6–3.3; cerebrovascular diseases RR 1.7, CI 1.1–2.7). Conclusions: Wide differences in the prevalence of cardiovascular diseases could be detected across immigrant groups. These findings represent a first step towards systematic chronic disease surveillance by ethnicity, a fundamental tool for shaping culturally-tailored prevention strategies. Highlights: Sparse data are available on the burden of cardiovascular diseases among immigrants in Europe. In Northern Italy the prevalence of diabetes was higher across all immigrant groups compared to Italians. Immigrants from South Asia were at very high risk of diabetes, dyslipidemia, and ischemic heart disease. Rates of hypertension, cerebrovascular diseases, heart failure were increased in Sub-Saharan Africans, especially females. The prevalence of chronic renal failure was higher among Asian and African immigrants.